Lowered parasympathetic activity in apparently healthy subjects with self-reported symptoms of pain: preliminary results from a pilot study - Koenig, Julian; Jarczok, Marc N.; Ellis, Robert J.; Warth, Marco; Hillecke, Thomas; Thayer, Julian F. (Pain practice, 2015)
OBJECTIVES: The aim was to evaluate differences in the autonomic nervous system (ANS) activity, indexed by heart rate variability (HRV) in apparently healthy subjects with self-reported symptoms of pain (SRSP) within an exploratory analysis. - METHODS: HRV data from 14 apparently healthy male individuals were analyzed to address potential differences in subjects with and without SRSP. SRSP was assessed using the four pain-related items from the symptom checklist (SCL-90R). Subjects were stratified based on the presence of SRSP. - RESULTS: Parasympathetic activity, indexed by pNN50, RMSSD, and high frequency (HF) spectrum of HRV, was lower in subjects with SRSP. Low frequency (LF) HRV and the LF/HF ratio were greater in subjects with SRSP. However, analysis of variance revealed no significant differences between the groups. Pearson correlations showed a correlation of pNN50, HF, LF, and LF/HF ratio and the presence and frequency of SRSP. Measures of parasympathetic activity (pNN50 and HF) were inversely associated with more SRSP, indicating that subjects with more frequent SRSP show decreased parasympathetic activity. - CONCLUSIONS: Consistent with evidence on changes in HRV in patients with clinical conditions of chronic or recurrent pain, this is the first study to show that healthy individuals who report symptoms of pain may have lower parasympathetic activity revealed by measures of HRV.